Electoral Law Reform in the Perspective of Responsive Justice: Comparative Law Between Indonesia, India, and Thailand - Kukuh Sudarmanto; Edi Pranoto; Vaibhav Jain (SASI)
Introduction: Elections are a vital democratic mechanism in channeling people's voices, electing leaders, and determining policies, with the principles of transparency, fairness, and effective oversight. Although there are still challenges in citizen participation, elections play a crucial role in peaceful transitions of power and socio-political stability.